2023
DOI: 10.1007/s00271-023-00878-3
|View full text |Cite
|
Sign up to set email alerts
|

Adequate supplemental irrigation amount during the critical period for yield in chia prevents reductions in radiation capture, radiation and water use efficiencies, and grain yield

Abstract: Chia is generally grown under rainfed conditions and is often under water de cit conditions during the critical period of owering and grain lling when yield is determined. Thus, the objective of this study was to determine how intercepted photosynthetically active radiation (iPAR), radiation use e ciency (RUE), water use e ciency (WUE), and grain yield were affected by different soil water availabilities during the critical period for yield in chia. Four levels of total available water (TAW) during the critica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Increased shade levels have been shown to reduce both RZT and evaporative water demand, leading to a decrease in both transpiration rates and soil water uptake by plants. Research has also shown how growers may make use of these phenomena to reduce incident solar radiation, wind speed, and water requirements for bell pepper ( Capsicum annuum ), chia ( Salvia hispanica ) and tomato ( Solanum lycopersicum ) production, leading to an increase in irrigation water use efficiency (Diez et al., 2023; Möller & Assouline, 2006). In a study of the effects of shade covers on heat stress in Herminio sweet pepper ( C. annuum ) during a winter–summer crop cycle, the temperature reduction caused by shading was found to improve both plant vegetative growth and leaf water status (López‐Marín et al., 2013).…”
Section: General Considerationsmentioning
confidence: 99%
“…Increased shade levels have been shown to reduce both RZT and evaporative water demand, leading to a decrease in both transpiration rates and soil water uptake by plants. Research has also shown how growers may make use of these phenomena to reduce incident solar radiation, wind speed, and water requirements for bell pepper ( Capsicum annuum ), chia ( Salvia hispanica ) and tomato ( Solanum lycopersicum ) production, leading to an increase in irrigation water use efficiency (Diez et al., 2023; Möller & Assouline, 2006). In a study of the effects of shade covers on heat stress in Herminio sweet pepper ( C. annuum ) during a winter–summer crop cycle, the temperature reduction caused by shading was found to improve both plant vegetative growth and leaf water status (López‐Marín et al., 2013).…”
Section: General Considerationsmentioning
confidence: 99%